A two-dimension medium band gap conjugated polymer based on 5, 10-bis(alkylthien-2-yl)dithieno[3, 2-d:3′, 2′-d′]benzo[1, 2-b:4, 5-b′]dithiophene: Synthesis and photovoltaic application. Issue 9 (1st September 2016) - Li, Jianfeng; Wang, Xu; Du, Sanshan; Tong, Junfeng; Zhang, Peng; Guo, Pengzhi; Yang, Chunyan; Xia, Yangjun
ABSTRACT: A two-dimension medium band gap copolymer poly{5, 10-bis(4, 5-didecylthien-2-yl)dithieno[2, 3- d :2′, 3′- d ′]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 7-diyl- alt -2, 5-di(3-octylthien-2-yl) thiophen-5, 5′-diyl}, named as PDTBDT-T-3T, was prepared by the palladium-catalyzed Stille cross coupling reaction and characterized. The resulting polymer exhibits good solubility in common organic solvents, excellent thermal stability, and extensive light absorption from 300 nm to 650 nm with an optical band gap of 1.92 eV, the highest occupied molecular orbital (HOMO) level of −5.03 eV and the hole mobility up to 1.92 × 10 −4 cm 2 ·V −1 ·s −1 . The power conversion efficiencies (PCEs) of 2.02%–3.19% have been achieved in the traditional PVCs for the copolymer. It should be noted that the PCEs of 4.2% for the inverted PVCs from the copolymer with PFN (poly[(9, 9-bis(3′-( N, N -dimethylamino)propyl)-2, 7-fluorene) -alt -2, 7-(9, 9-dioctyl- fluorene)]) as cathode modifying interlayer, were similar with the PCEs of 4.39% for the inverted PVCs from P3HT:PC71 BM at the same condition. These results indicated that the copolymer could be used as potential candidate for P3HT.